Nanoparticles Targeting Macrophages as Potential Clinical Therapeutic Agents Against Cancer and Inflammation - Hu, Guorong; Guo, Mengfei; Xu, Juanjuan; Wu, Feng; Fan, Jinshuo; Huang, Qi; Yang, Guanghai; Lv, Zhilei; Wang, Xuan; Jin, Yang (Frontiers in Immunology, 2019)
With the development of nanotechnology, significant progress has been made in the design and manufacture of nanoparticles (NPs) for use in clinical treatments. Meanwhile, recent increases in our understanding of the central role of the macrophages in the context of inflammation and cancer have reinvigorated interest in macrophages as a drug target. Macrophages serve an integral role in maintaining the steady state of the immune system and are involved in the processes of cancer and inflammation. Thus, nanoparticles tailored as needed to accurately target macrophages have the potential to transform disease treatment. Herein, we firstly present a brief background information of NPs as drug carriers including but not limited to types of nanomaterial, their biological properties and their advantages in clinical application. Then macrophage effector mechanisms and recent NP-based strategies aiming at targeting macrophages by eliminating or re-educating macrophages in inflammation and cancer are summarized. Additionally, the development of nano-carriers targeting macrophages for disease diagnosis are also discussed. Finally, the significance of macrophage-targeting nanomedicine is highlighted, with the goal of facilitating future clinical translation.